Third Ethiopia Economic Update : Strengthening Export Performance through Improved Competitiveness - World Bank Group (Washington, DC, 2014)
Rising exports contributed to Ethiopia’s remarkable growth performance over the past decade. Buoyed by favorable external conditions, exports also helped create jobs and earn much-needed foreign exchange. The way Ethiopia created and nurtured a high-value horticulture industry and expanded its air services exports was an encouraging example of “self-discovery.”